The Effectiveness of Monitoring Mechanisms for Constraining Earnings Management: A Literature Survey for a Conceptual Framework - Saleem, Faiza; Alifiah, Mohd Norfian; Tahir, Muhammad Sohail (International Journal of Economics and Financial Issues, 2016)
Recently, financial crisis and high profile corporate scandals in the United States, Europe and East Asia, have brought corporate governance and audit quality issues to the forefront in developing countries, emerging markets and transitional economies. In fact, the main issue involves manipulation of accounting data which lose investor confidence and trust in the financial reports. In order to enrich investor confidence and trust regarding financial reporting quality, firms need to adopt effective monitoring mechanisms. In relation to that, this paper proposes a conceptual framework to investigate the role of regulatory mechanisms concentrating on corporate governance and external audit for mitigating earnings management. Evidence from previous studies supports the proposed model. Hence, the extant study argues that firms with effective monitoring mechanisms in the form of corporate governance and external audit are less likely to allow earnings management because opportunistic earning’s cause uncertainty about the economic value of a firm. Keywords: Corporate Governance, Bankruptcy, External Audit, Earnings Management. JEL Classifications: G3, G33, G39, G32